Physical activity has a stronger correlation with arterial stiffness than strength, balance, or BMI in an older population - Hill, Hannah; Elliot, Catherine A.; Lizamore, Catherine A.; Hamlin, Michael J. (Frontiers in Aging, 2023)
Background: Arterial stiffness is associated with an array of debilitating health conditions. While exercise typically has beneficial effects on both arterial stiffness and overall health, more research is needed to understand the associations of different types of fitness indices with arterial stiffness. Aim: To investigate the relationship between balance, strength, cardiovascular fitness and physical activity with arterial stiffness (as measured by pulse wave velocity (PWV)) in older adults. Method: Eighty retirement-village residents (24 males, 56 females, age: 78.2 ± 6.4 years, weight: 69.4 ± 12.5 kg, height: 162.9 ± 8.5 cm) completed the Yale Physical Activity Survey, PWV measurement, 30-second sit-to-stand leg strength test, hand grip strength assessment, 4-stage balance test, and a 6-minute walk fitness test. The number of exiting risk factors (smoking, previous heart incidents, previous stroke(s), having hypertension, or taking anti-hypertension medication) were tallied. Pearson’s correlations were used to assess the relationship between PWV and health and fitness parameters. Results were interpreted using qualitative inference. Results: The number of risk factors (r = 0.57, p < 0.001), age (r = 0.51, p < 0.001) and systolic blood pressure (r = 0.50, p = 0.001) had strong, harmful associations with PWV. Total physical activity minutes/week (r = -0.31 p = 0.01), total energy expenditure Kcal/week (r = -0.30, p = 0.01), and the 6-minute walk test (r = -0.29, p = 0.01) had a moderate, beneficial association with PWV, while sit-to-stand (r = -0.27, p = 0.02) and balance (r = -0.27, p = 0.01) had a weak, beneficial association with PWV. Hand grip strength (r = 0.02, p = 0.94) and body mass index (r = -0.04, p = 0.75) had no significant associations with PWV. Discussion: All measured fitness indices had beneficial associations with PWV. However, having more risk factors, increased age, and higher systolic blood pressure had significant (harmful) associations with PWV in our older population. Conclusion: Controlling cardiovascular risk factors, especially high systolic blood pressure, is likely to have the largest beneficial effect on PWV. Improving general physical activity, including walking capacity, may prove beneficial in improving PWV in an older population.